Early Postoperative Complications and Factors Associated with Early vs Late Discharge of Patients Undergoing Colporrhaphy for Pelvic Organ Prolapse: A National Report. Issue 4 (17th July 2021) - Norton, J. Corbin; Khalil, Mahmoud I.; Bhandari, Naleen Raj; Acharya, Mahip; Payakachat, Nalin; Davis, Rodney; Mahdy, Ayman; Raheem, Omer A.; Hanberry, Jordan; Eltahawy, Ehab
Abstract: Introduction: Pelvic organ prolapse is a highly prevalent condition that is commonly managed with surgical intervention. Our purpose was to determine associated factors and postoperative morbidity rates of early (≤1 day) vs late (>1 day) hospital discharge after outpatient colporrhaphy. Methods: From the National Surgical Quality Improvement Program® database, 11, 652 female patients who received colporrhaphy between 2005 and 2016 were identified; 3, 728 were stratified into the early discharge group and 7, 924 into the late discharge group. Patient characteristics, surgical data and 30-day postoperative complications were recorded, and variables were compared between groups. Results: In comparison to the late discharge group, the early discharge group had a shorter mean operating time (p <0.001) and overall was less likely to suffer from 30-day morbidity (OR 0.67 [95% CI 0.55–0.82]), reoperation (OR 0.59 [95% CI 0.39–0.90]) or readmission (OR 0.40 [95% CI 0.26–0.90]). Factors independently associated with a lower likelihood of early discharge included age ≥55 years, higher body mass index, White race, current smoker, American Society of Anesthesiologists® classification IV/V and longer operating time. Increased likelihood of early discharge was associated with receiving colporrhaphy after 2012 and posterior colporrhaphy. Conclusions: Patients discharged from the hospital early had lower rates of postoperative morbidity than those discharged later. Early discharge was associated with procedures performed after 2012 and with isolated posterior colporrhaphy. Longer hospital stays were associated with longer operating times and older age, White race, obesity, comorbidities and history of smoking.